THE INFLUENCE OF LIVE STREAMING AND CUSTOMER REVIEWS ON PURCHASING DECISIONS FOR KEMAIU SHAMPOO PRODUCTS - Purba, Ruth Agita; Mandasari, Virginia (Yayasan Education and Social Center, 2024)
This study aims to find how much influence live streaming and customer reviews have on purchasing decisions for